Tuesday
March 28, 2017

Post a New Question

Posted by on .

how do you solve this by substitution:
step by step

1. 5x-y=16
5x+2y=13

2. 3x-3y=9
2x-4y=-16

3. x=-6y
y=2/3x+5

thank you!

  • algebra! - ,

    3. x = -6y

    y = 2/3x + 5

    y = 2/3(-6y) +5

    y = -4y + 5

    5y = 5

    y = 1

    Substitute -6y for x in second equation and solve for y. Insert that value into the first equation and solve for x. Check by inserting both values into the second equation.

    Use the same process for the first two equations.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question